2011
DOI: 10.1242/dev.058016
|View full text |Cite
|
Sign up to set email alerts
|

Conditional ablation of Pten in osteoprogenitors stimulates FGF signaling

Abstract: SUMMARYPhosphatase and tensin homolog deleted on chromosome ten (PTEN) is a direct antagonist of phosphatidylinositol 3 kinase. Pten is a well recognized tumor suppressor and is one of the most commonly mutated genes in human malignancies. More recent studies of development and stem cell behavior have shown that PTEN regulates the growth and differentiation of progenitor cells. Significantly, PTEN is found in osteoprogenitor cells that give rise to bone-forming osteoblasts; however, the role of PTEN in bone de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 46 publications
(62 reference statements)
0
40
0
Order By: Relevance
“…Conditional deletion of PTEN, a phosphatase that suppresses PI3K/ Akt signaling upstream of Phlpp1, in limb progenitor cells enhanced Fgf18 expression (36). The authors attributed this regulation to decreased levels of FoxO1, which represses Fgf18 promoter activity (36). We also found that disrupting the substrate binding ability of Phlpp1 enhances Fgf18 expression, and that this effect is antagonized by expression of an Akt-insensitive FoxO1 mutant.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Conditional deletion of PTEN, a phosphatase that suppresses PI3K/ Akt signaling upstream of Phlpp1, in limb progenitor cells enhanced Fgf18 expression (36). The authors attributed this regulation to decreased levels of FoxO1, which represses Fgf18 promoter activity (36). We also found that disrupting the substrate binding ability of Phlpp1 enhances Fgf18 expression, and that this effect is antagonized by expression of an Akt-insensitive FoxO1 mutant.…”
Section: Discussionmentioning
confidence: 62%
“…FoxO1 Represses Fgf18 Expression in Chondrocytes-FoxO1 represses Fgf18 transcription (36) and therefore may link enhanced Akt2 signaling to Erk1/2 activation in Phlpp1 Ϫ/Ϫ chondrocytes. To test this hypothesis, a Phlpp1 deletion mutant (Phlpp1⌬C) that inhibits interactions between Akt2 and Phlpp1 was introduced in chondrogenic ATDC5 cells (18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PTEN can modulate glioma response to the inhibition of HGF/c-Met signaling pathway [45], and PTEN loss amplifies c-Met-induced glioblastoma malignancy [46]. In addition, PTEN loss also induces autocrine FGF signaling to promote skin tumorigenesis [47], and lack of PTEN in osteoprogenitor cells resulted in increased osteoblast numbers and expanded bone matrix by stimulating FGF signaling [48]. Thus, in our study, up-regulation of PTEN expression in CAFs inhibited gastric cancer cell migration and invasion, which is probably mediated through regulating the expression and secretion of these growth factors and chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…We used miRanda (19), PicTar (20), and TargetScan (21) to predict the targets of miR-188. Among the predicted genes, we chose 6 for further analysis-histone deacetylase 9 (Hdac9), RPTORindependent companion of MTOR complex 2 (Rictor), phosphatase and tensin homolog (Pten), zinc finger protein 281 (Znf281), GLIS family zinc finger 3 (Glis3), and ephrin B2 (Efnb2)-which had been reported to participate in bone metabolism (22)(23)(24)(25)(26)(27)(28). Overexpression or inhibition of miR-188 changed endogenous levels of HDAC9 and RICTOR protein, but not the others ( Figure 8A).…”
Section: Aging Induces Mir-188 Expression In Bmscsmentioning
confidence: 99%